Understanding COVID-19 vaccine hesitancy in vasculitis patients - Butt, Imama N.; van Eeden, Charmaine; Kovacs Burns, Katharina; Saxinger, Lynora; Clifford, Alison; Redmond, Desiree; Cohen Tervaert, Jan Willem; Yacyshyn, Elaine (Frontiers in Public Health, 2023)
Objective To identify the factors that impact COVID-19 vaccine decision-making in vaccine-hesitant vasculitis patients, and compare their perceptions with other rheumatology patients, given existence of data suggesting rheumatology patients may have disease-specific factors that influence their COVID-19 vaccine decision-making. Methods This cross-sectional study surveyed adult rheumatology patients from the Kaye Edmonton Clinic Rheumatology Clinic, in Canada, between June and August 2021, using an anonymous online questionnaire. Survey responses were analyzed for statistical differences using chi-square analysis. Results The COVID-19 Vaccine Perceptions Survey had a response rate of 70.9%. Of the total 231 respondents, 103 patients were diagnosed with vasculitis. At the time of the survey, 10.6% of vasculitis patients refused to receive a COVID-19 vaccine compared to 6.3% for other rheumatology patients. Compared to other rheumatology patients, vaccine-hesitant vasculitis patients were significantly more concerned about almost every aspect of available COVID-19 vaccines [e.g., safety (p < 0.001), components (p < 0.001)], and feared that they could contract SARS-CoV-2 from a vaccine (p < 0.001). These vaccine-hesitant patients were also significantly less pleased with the government's pandemic response, less confident in healthcare team-provided information (p < 0.001), and more likely to report that healthcare providers had no role in their COVID-19 vaccine decision-making (p < 0.001). Conclusion Vaccine-hesitant vasculitis patients may have multiple considerations influencing COVID-19 vaccine hesitancy, including vaccine and disease-specific concerns, along with unfavorable perceptions of the healthcare system (government and healthcare providers). Healthcare providers can address some of these concerns by initiating patient-centered discussions around immunizations to help support educated decision-making.